Formação de professores e educação antirracista a partir de narrativas (auto)biográficas - Silva, Rafaela Fonseca da (Brasil, 2024)
The research is inserted in the field of Teacher Training and Anti-Racist Education, it is dedicated to an investigation through the experiences of a quilombola researcher and understanding the need to be renewed and implemented according to laws 10.639/03 and 11.645/08 in everyday life school. The assumptions of Anti-Racist Education through the (auto) biographical narratives that are demonstrated here seek to criticize the non-execution of anti-racist education in everyday school life and the challenges that black teachers face in their professional training and practice. The objective of the research is to analyze the role of (auto) biographical narratives in the training of black teachers for Anti-Racist Education. This exercise will enable a reflection on the author’s experience in this struggle. And from this set of analyses, build an educational product that promotes the appreciation of the (auto) biographical narrative in the training of black teachers for anti-racist education. The following authors were identified for the theoretical framework: a) on issues linked to racism: Abdias Nascimento, Djamila Ribeiro, Silvio de Almeida, Nilma Lino Gomes, Lélia Gonzalez, Conceição Evaristo, Kabengale Munanga, Chimamanda Nigozi Adiche, bell hooks; b) on teacher training issues: António Nóvoa, Francisco Ibernón, Donald Schön, Isabel Alarcão, Carlos Libâneo; c) on issues related to (auto)biographical narratives: Marie-Christine Josso; Elizeu Clementino Souza, Maria da Conceição Passeggi, D. Jean Clandini, Michael Connelly.The approach used in this research was qualitative, as it tries to understand how the phenomenon happens through the approach of language, its symbols, senses, meanings and representations. To achieve the objectives of this research. The results served as a basis for developing an initial training proposal for black teachers from Quilombo Urbano de São Benedito with a focus on racial literacy. To publicize this proposal, an Educational Product entitled “Sankofa” Anti-Racist Teacher Training Book was created, presenting a contemporary discussion on anti-racist education based on primarily black literature with the participation of black teachers from Quilombo Urbano do Barranco de São Benedito who were the subjects of this research.